Functional Analysis of Ion Transport Properties and Salt Tolerance Mechanisms of RtHKT1 from the Recretohalophyte Reaumuria trigyna. (15th September 2018) - Li, Ningning; Du, Chao; Ma, Binjie; Gao, Ziqi; Wu, Zhigang; Zheng, Linlin; Niu, Yiding; Wang, Yingchun
Abstract: Reaumuria trigyna is an endangered recretohalophyte and a small archaic feral shrub that is endemic to arid and semi-arid plateau regions of Inner Mongolia, China. Based on transcriptomic data, we isolated a high-affinity potassium transporter gene ( RtHKT1 ) from R . trigyna, which encoded a plasma membrane-localized protein. RtHKT1 was rapidly up-regulated by high Na + or low K + and exhibited different tissue-specific expression patterns before and after stress treatment. Transgenic yeast showed tolerance to high Na + or low K +, while transgenic Arabidopsis exhibited tolerance to high Na + and sensitivity to high K +, or high Na + –low K +, confirming that Na + tolerance in transgenic Arabidopsis depends on a sufficient external K + concentration. Under external high Na +, high K + and low K + conditions, transgenic yeast accumulated more Na + –K +, Na + and K +, while transgenic Arabidopsis accumulated less Na + –more K +, more Na + and more Na + –K +, respectively, indicating that the ion transport properties of RtHKT1 depend on the external Na + –K + environment. Salt stress induced up-regulation of some ion transporter genes ( AtSOS1 / AtHAK5 / AtKUP5 - 6 ), as well as down-regulation of some genes ( AtNHX1 / AtAVP1 / AtKUP9 - 12 ), revealing that multi-ion–transporter synergism maintains Na + /K + homeostasis under salt stress in transgenic Arabidopsis. Overexpression of RtHKT1 enhanced K + accumulation and prevented Na + transport from roots to shoots, improved biomass accumulation and Chl content in salt-stressed transgenic Arabidopsis. The proline content and relative water content increased significantly, and some proline biosynthesis genes ( AtP5CS1 and AtP5CS2 ) were also up-regulated in salt-stressed transgenic plants. These results suggest that RtHKT1 confers salt tolerance on transgenic Arabidopsis by maintaining Na + /K + homeostasis and osmotic homeostasis.